A Case Report on Bronchial Asthma with Myopathy - Islam, SM Shahidul; Lima, Rehana Akter (Archives of Clinical and Medical Case Reports, 2022)
Muscle disease is referred to as myopathy. As a result, the muscles are less efficient than they might be. When muscles don't grow correctly, are injured, or are missing vital components, this might happen. Muscle atrophy is common in patients who have had Bronchial Asthma with Myopathy for a long time. Muscles lose mass and strength as a result of this fading away. We recently treated a patient who was experiencing some of the same issues. We suggested a Brain MRI and total spine screening to the patient which indicated hypoplasticity in the left transverse sinus. An X-Ray of the chest indicated that the left inferior nasal turbinate had expanded. Traditional therapies like acupuncture and massage, as well as modern techniques like multipurpose equipment and physiotherapy, were chosen to treat our patients. Our patient had wonderful success with these strategies. The procedure for the patient’s treatment has been completed. At the end of the 12th day of chest treatment, the patient was completely free of breathlessness. On the 10th day of acupuncture, the patient’s low back discomfort began to improve. At the end of the 20th day of therapy, the patient's headache begins to improve. Moreover, the authors believe that it is the first successful reported case in Bangladesh using these techniques.